Evaluation of executive functions in children between (6-11) years old, based on the BRIEF test, an Arabic version for parents - Boukhdenna, Mounir (Journal of Human Sciences, 2025)
This research aims to present a screening tool for executive function disorders, version for parents, containing 82 items intended for children (6-11 years old) It allows the observation of these functions through apparent behaviors during the last six months , which are related to emotional regulation, working memory, planning, inhibition and cognitive flexibility, in the environment in which the child lives. Where we translated the instruction and the items that are behaviors practiced by the child in Arabic addressed to the parents of BRIEF, It is with the aim of its compatibility with the Algerian environment and the characteristics of its members. by presenting it to referees with scientific experience and qualifications, and due to the absence of the cultural factor, the observations were taken into account and minor adjustments were made to the tool, taking into account the cultural level of each family.